Hydrodeoxygenation of lignin-derived phenolic compounds over Ru/TiO2 catalyst: Effect of TiO2 morphology. (1st February 2023) - Zhong, Zhuojie; Li, Junxuan; Jian, Minyin; Shu, Riyang; Tian, Zhipeng; Wang, Chao; Chen, Ying; Shi, Ning; Wu, Yanxue
Highlights: Ru/TiO2 catalysts with different morphology were compared in guaiacol HDO. Ru/TNP catalyst with TiO2 nanosphere exhibited the best reaction performance. Large surface area improved Ru dispersion and led to a good hydrogen adsorption. An abundance of medium strength acid sites promoted the deoxygenation step. Hydrocarbon content in lignin-oil increased from 11.1% to 60.8% after HDO. Abstract: Hydrodeoxygenation (HDO) reaction is a necessary refinery process for lignin-derived phenolic compounds to be used as high quality liquid fuels. Catalyst morphology makes a big difference on the HDO performance through changing the properties of metal site and acid site, while the catalytic mechanism is still not very clear. In this work, four kinds of Ru/TiO2 catalysts with different morphology were prepared by photochemical method and all of them achieved a high Ru metal dispersion. A series of catalyst characterizations were carried out, including XRD, BET, SEM, TEM, H2 -TPD and NH3 -TPD, in order to explore the crystal structure, surface property, Ru metal dispersion, hydrogen adsorption capacity as well as acid properties. Results showed that Ru/TNP catalyst possessed a large surface area, an abundance of medium strength acid sites and a good hydrogen adsorption capacity. The HDO performances on lignin-derived phenolic compounds were also compared, in which Ru/TNP catalyst presented the best HDO performance. The guaiacol conversion and the selectivity of cyclohexane product were both close to 100 % at 250 °C under 1 MPa hydrogen pressure. Moreover, the content of hydrocarbons increased from 11.1 % to 60.8 % in the lignin-oil upgrading process.